LEGITIMACY AND AUTHORITY OF FOLK MEDICINE PRACTITIONERS IN POST-SOVIET KAZAKHSTAN - Kopbayev, Nurdaulet (Nazarbayev University School of Sciences and Humanities, 2021)
The thesis describes traditional medical practices in Kazakhstan. The research project applies the Weberian concept of “legitimacy” to folk healing in the context of Kazakhstan. The research project has several objectives. Firstly, the paper covers the historical and modern representation of folk medicine by the state and Kazakhstani society along with the commercialization process of folk healing. Secondly, it classifies different types of healers providing their services and discusses the role of religion in Kazakhstan folk medicine. Lastly, the analytical part of this project explains the dynamics behind the legitimization of folk medical practices by healers, patients and the state. The project focuses on identifying the ways in which traditional Kazakhstani healers wield legitimacy into their practices. The purpose of this thesis is to analyze the legitimation strategies employed in non-biomedical healing practices in contemporary Kazakhstan. Folk medicine in Kazakhstan has a long history of different social and political periods that have transformed it into its current shape. Through those events folk healing has become an inseparable part of a Kazakh culture. The social perception is that this sector of medicine has a huge potential to grow in the foreseeable future. There are different types of folk healers in Kazakhstan that vary depending on their specialization. Although there are lots of similarities among healers, different healers tend to use different techniques to legitimize their practices. According to the results of the project, when deciding to approach a folk practitioner, the most influential factor for the Kazakhstani society is the traditional authority of a certain healer. Individual characteristics and the political implications also play a significant role in providing legitimacy to folk healers, though they were not given as much emphasis by the healer respondents as legitimation through traditional knowledge.
Keywords: Type of access: Open Access; folk medicine; post-soviet Kazakhstan